Government Debt, Life-Cycle Income and Liquidity Constrains : Beyond Approximate Ricardian Equivalence - Symansky, Steven (IMF Working Papers; Working Paper ;, 1996)
Evans (1991) has demonstrated that Blanchard's (1985) finite-horizon model obeys approximate Ricardian equivalence. We show that this result is determined largely by an unrealistic assumption that labor income grows monotonically over a consumer's entire lifetime. Introducing more realistic lifetime earnings profiles, we find that the effects of government debt on the real interest rate and the capital stock become considerably larger. In particular, leaving aside the effects of distortionary capital taxation, the extended model with liquidity constraints predicts that real interest rates would decline by about 150-200 basis points if government debt were eliminated completely in all OECD countries.